From bench to bedside: targeting ferroptosis and mitochondrial damage in the treatment of diabetic cardiomyopathy - Liu, Bin; Jin, Qing; Sun, Yi Kang; Yang, Zhi Ming; Meng, Ping; Zhang, Xi; Chen, Qiu; Gan, Pin; Zhao, Tao; He, Jia Ji; He, Gui Ping; Xue, Qiang (Frontiers in Endocrinology, 2025)
Diabetic cardiomyopathy (DCM) is a common and fatal cardiac complication caused by diabetes, with its pathogenesis involving various forms of cell death and mitochondrial dysfunction, particularly ferroptosis and mitochondrial injury. Recent studies have indicated that ferroptosis and mitochondrial damage play crucial roles in the onset and progression of DCM, though their precise regulatory mechanisms remain unclear. Of particular interest is the interaction between ferroptosis and mitochondrial damage, as well as their synergistic effects, which are not fully understood. This review summarizes the roles of ferroptosis and mitochondrial injury in the progression of DCM and explores the molecular mechanisms involved, with an emphasis on the interplay between these two processes. Additionally, the article offers an overview of targeted drugs shown to be effective in cellular experiments, animal models, and clinical trials, analyzing their mechanisms of action and potential side effects. The goal is to provide insights for future drug development and clinical applications. Moreover, the review explores the challenges and prospects of multi-target combination therapies and personalized medicine interventions in clinical practice to offer strategic guidance for the comprehensive prevention and management of DCM.